THE IMPLEMENTATION OF M-LEARNING IN LEARNING CALCULUS II - Sulastri, Yayu Laila; Lestari, Zubaedah Wiji; Hakim, Luki Luqmanul (PEOPLE: International Journal of Social Sciences, 2015)
Calculus II is a course containing basic concepts of mathematics which is required to follow the following courses: Calculus III and Differential Equations, Vector Analysis, Real Analysis, and Numerical Methods. The researchers examine that many students found difficulties in this subject and it resulted in low learning outcomes.One of the advance or progress in the field of education is shown by the process of learning that no longer teacher-centered but student-centered. The issue requires the experts to develop learning process which implied to student centered learning. Mobile learning (m-learning) is one of models that suit with the issue. The purpose of this paper is (a) to describe the implementation of m-learning in learning calculus II, and (b) to determine and obtain an overview of the mobile-based learning process. The methodof this study is Research and Development (R&D). The respondents in this study is the fourth semester students, 2014/2015 year academic. This model of learning combines some elements such as technology device, social aspect, and the students themselves. The process of learning is begining by downloading the learning material application to be installed into mobile device based of OS Android, Windows, and daniOS. After finishing the installation, the users can start to browse the material. The facilities provided by the material supplier are different, depends on the needs and the purpose to be achievedto browse the material. The facilities provided by the material supplier are different, depends on the needs and the purpose to be achieve.